Motivational and Perceptual Factors for Choosing Teaching as a Career in Chile: Sex Differences - Gonzalez Sanzana, Alvaro; García, Katherine Acosta; Carreño, Jorge Valenzuela; Ossandón, Jorge Miranda; Fuentes, Lidia Valdenegro (My University, 2022)
This paper analyzes the similarities and differences by sex in the motivational variables for choosing a teaching career. We set out to determine the motivational variables influencing student teachers to opt for teaching careers according to sex. Nine hundred and ninety-five student teachers from four Chilean universities participated in this study. Female respondents constituted 65.7% of those who responded to the research instrument (n = 654), while male respondents comprised 34.3% (n = 341) of the sample. The study used the FIT-Choice (factors influencing teaching choice) Scale. This paper presents differential evidence by sex regarding the motivations that the literature has recognized as relevant for selecting a teaching career in Chile. The comparative results showed that women are more motivated than men for their studies, perceive themselves as having greater capacities for teaching, and are more satisfied with this career choice. Intrinsic value is the main motivational factor that explains satisfaction with career choices for both sexes. However, it appears more strongly in men. It is followed in importance by social utility value, perceived ability, and previous teaching-learning experiences. The positive relationship between the perceived demands of the profession and the desire to pursue a teaching career stands out among men. The implications of these findings are discussed.
Keywords: fit-choice scale; higher education; motivation; preservice teachers; sex